Acute airway obstruction due to Ascaris Lumbricoides in a ventilated child - Srinovianti, Noerdin; Mat Nor, Mohd Basri (Faculty of Medicine, International Islamic University Malaysia, 2002)
Ascaris lumbricoides or roundworm is a nematode causing infestation in about 1.3 billion people worldwide. We report a case of a 7-year-old patient who had head injury. He was admitted to the intensive care unit for mechanical ventilation after craniotomy and evacuation of extradural haemorrhage at the left temporoparietal area. While weaning off mechanical ventilation two days after admission, he developed an acute airway obstruction. Flexible bronchoscopy revealed a tube like foreign body obstructing the right and left bronchus. Emergency rigid bronchoscopy under general anaesthesia extracted an eight-centimetre long Ascaris lumbricoides. The patient’s ventilation and oxygenation improved drastically and he was discharged home 3 weeks later.